RANCANG BANGUN MEDIA PEMBELAJARAN BAHASA DAN HURUF JAWA BERBASIS ADOBE FLASH CS6 - Heru Supriyono; Endah Sudarmilah; Umi Fadlilah; Endah Tri Rahayu; Agus Purwohartono (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The drastically development in science and technology in the area of electronics, computer and informatics enable people to develop multimedia application including learning media. This paperdiscusses research had been done on development of Adobe Flash CS6 learning media forJavanese alphabet and language. The aim of the research is to design and develop the learningmedia and test its performance. The developed application has useful features to improve student’sunderstanding such as description, animation of how to write Javanese alphabet, sound applicationhow to read Javanese alphabet, sample how to write sentence using Javanese alphabet and quiz.The application program had been tested on diferent computers and also tested for Javaneseteachers and elementary school students. The results showed that the application program wasable to work very well in diferent devices and most respondents, in general, said that theapplication program is satisfying to be used in the Javanese learning for elementary student.Key words: Multimedia, Adobe Flash CS6, Javanese language learning, aksara Jawa